Energy expenditure and slow-wave sleep in runners: Focusing on reproductive function, chronic training, and sex - Akiko Uchizawa; Haruka Osumi; Simeng Zhang; Katsuhiko Yajima; Airi Funayama; Emi Kondo; Yoko Suzuki; Yoshiaki Tanaka; Insung Park; Yasushi Enomoto; Naomi Omi; Kumpei Tokuyama; et al. (iScience)
Summary: This comparative study focused on chronic exercise training, menstrual cycle, menstruation, and sex related with slow-wave sleep and energy expenditure (EE) during sleep in runners and controls. Participants included 26 highly trained runners (9 males, 8 amenorrheic females, and 9 menstruating females) and 20 controls (10 males and 10 menstruating females) aged 21 ± 2 years. Sleeping metabolic rate and EE during slow-wave sleep were 2.7% and 3.9% higher in the luteal than the follicular phase for female runners. Significant interactions were found between the 8-h time course adjusted EE and menstruation, exercise training, and sex. Sleep stage durations did not differ between groups. Interestingly, amenorrheic runners did not suppress sleeping and overnight metabolic rates, suggesting that EE in sleep may not be a causative factor for amenorrhea in runners. This study highlights the complex relationship between chronic exercise, menstrual cycle, and sex on EE during sleep.